Mobilized Multipotent Hematopoietic Progenitors Promote Expansion and Survival of Allogeneic Tregs and Protect Against Graft Versus Host Disease - D’Aveni, Maud; Notarantonio, Anne-Béatrice; Agbogan, Viviane A.; Bertrand, Allan; Fouquet, Guillemette; Gastineau, Pauline; Garfa-Traoré, Meriem; De Carvalho, Marcelo; Hermine, Olivier; Rubio, Marie-Thérèse; Zavala, Flora (Frontiers in Immunology, 2021)
Allogeneic Hematopoietic Stem Cell Transplantation (Allo-HSCT) is routinely performed with peripheral blood stem cells (PBSCs) mobilized by injection of G-CSF, a growth factor which not only modulates normal hematopoiesis but also induces diverse immature regulatory cells. Based on our previous evidence that G-CSF-mobilized multipotent hematopoietic progenitors (MPP) can increase survival and proliferation of natural regulatory T cells (Tregs) in autoimmune disorders, we addressed the question how these cells come into play in mice and humans in an alloimmune setting. Using a C57BL/6 mouse model, we demonstrate that mobilized MPP enhance the immunosuppressant effect exerted by Tregs, against alloreactive T lymphocytes, both in vitro and in vivo. They do so by migrating to sites of allopriming, interacting with donor Tregs and increasing their numbers, thus reducing the lethality of graft-versus-host disease (GVHD). Protection correlates likewise with increased allospecific Treg counts. Furthermore, we provide evidence for a phenotypically similar MPP population in humans, where it shares the capacity to promote selective Treg expansion in vitro. We postulate that G-CSF-mobilized MPPs might become a valuable cellular therapy to expand donor Tregs in vivo and prevent GVHD, thereby making allo-HSCT safer for the treatment of leukemia patients.